Electrochemical properties of Al doped Li(Ni1/3CO 1/3Mn1/3)O2 - Kim, S.H.; Shim, K.B.; Han, K.R.; Kim, C.-S. (Solid State Phenomena, 2007)
Al doped Li(Ni1/3Co1/3Mn1/3Al x)O2 (x=0.005, 0.01, 0.05) and Li(Ni 1/3-x/2Co1/3Mn1/3-x/2Alx)O 2 (x=0.01, 0.05) cathode materials for lithium ion batteries were synthesized using an ultrasonic spray pyrolysis and heat treatment. The substitution with Al reduced the content of Mn3+, promoted grain growth, and broadened the particle size distribution of synthesized powders. The initial discharge capacity of cells made with 0.5 mol% Al doped Li(Ni 1/3Co1/3Mn1/3-0.005Al0.005)O 2 powder was as high as that of the undoped (∼180 mAhg -1, 3.0-4.5 V), and showed an excellent cycle stability. The improvement of the cycle stability was considered to be due to the decrease of Mn3+ in Li(Co1/3Ni1/3Mn1/3-xAl x)O2 by Al doping.